Application of agent in electronic commerce - Loke, Paul Daniel Yu Ming. (2008)
The mobile agent paradigm is gaining importance and visibility as a new approach to electronic commerce. Its inherent advantages, such as the autonomy, reduced network usage and dynamic service updates make it an attractive alternative to the traditional electronic commerce model.